Semiotic analysis of the relationship between architectural forms and the urban phenomena of segregation and gentrification in Mexico City - Carolina Magaña Fajardo; Mónica Solórzano Zavala (Economia Creativa, 2023)
This paper delves into gentrification and segregation in 21st-century Mexico City, connecting a critical visual photo-documentation approach to understanding contemporary urban relationships and social identities. It integrates Charles Morris' triadic model (syntactic, semantic, and pragmatic levels) in analyzing photo-documentary images. These models help identify urban elements as visual narratives, contributing to segregation and gentrification. The study focuses on Mexico City, specifically the San Nicolás Totolapan neighborhood, using this method to interpret images in context and assess their impact on constructing meanings and representations. The research outcomes offer valuable insights for informed decision-making in architectural and urban design. This work contributes to understanding and addressing the issues of gentrification and segregation in Mexico City's urban landscape.